Pengaruh strategi pemasaran terhadap kepuasan pengunjung River Tubing Lembah Niti - Setiawan, Agus Dadan; Surtiani, Ani; Dzulfikar, Irfan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study was to analyze the role of the marketing mix strategy in influencing visitor satisfaction in River Tubing, Niti Valley, Subang Regency. This research uses a quantitative approach, with an explanatory survey method. Determination of the sample was calculated using the Slovin formula from the population, namely the average monthly visitor at the River Tubing Lembah Niti (PT. Sari Ater) tourist attraction, namely 996 with an error rate of 10%, so that the sample in this study was 91 respondents. Methods of data analysis using simple linear regression analysis by testing the hypothesis t test. The results of the study concluded that the variable marketing mix has an effect on visitor satisfaction in River Tubing, Niti Valley, Subang Regency. The magnitude of the influence of the marketing mix is 0.790 or 79 percent, and the remaining 21 percent is influenced by other factors.